Cultural Communication and Its role in the Educational Performance of Instructors of The College of Fine Arts - Ahmed, Zahraa Saeb; Hassan, Najlaa Khudair (Al-Adab Journal, 2022)
The educational institution has a role in preparing a conscious generation by providing them with knowledge, habits and concepts that qualify them for social adaptation, and the teacher is a fundamental pillar of the educational process, as his role is not limited to the delivery of information to students, but goes beyond that to the numbers of mentally, psychologically and socially good individuals. , The educational performance of the teaching became the basis of the educational process, from this point on, our study was an attempt to reveal the Cultural Communication and Its role in the educational performance of Instructors of the college of fine arts. The first chapter included a definition of the limits of research and a definition of the terminology contained. As for the second chapter, it was represented by the theoretical framework and previous studies, and it included two topics: The first: cultural communication, its types, and characteristics, while the second topic included: educational performance. As for the third chapter, it included the research procedures as the research community, the research sample, the research tool, and the validity and reliability of the tool, and then the fourth chapter included the results of the research, conclusions, recommendations, and suggestions .Finally, the two researchers reached several results, including: - That cultural communication helped raise the value of the teaching’s artistic appreciation by communicating with art galleries of artists belonging to different cultures and having dialogue with them, thus contributing to crystallizing new ideas in his artistic field.